Renewable and non-renewable exergy costs and CO2 emissions in the production of fuels for Brazilian transportation sector. (August 2015) - Flórez-Orrego, Daniel; da Silva, Julio A.M.; Velásquez, Héctor; de Oliveira, Silvio
Abstract: An exergy and environmental comparison between the fuel production routes for Brazilian transportation sector, including fossil fuels (natural gas, oil-derived products and hydrogen), biofuels (ethanol and biodiesel) and electricity is performed, and the percentage distribution of exergy destruction in the different units of the processing plants is characterized. An exergoeconomy methodology is developed and applied to properly allocate the renewable and non-renewable exergy costs and CO2 emission cost among the different products of multiproduct plants. Since Brazilian electricity is consumed in the upstream processing stages of the fuels used in the generation thereof, an iterative calculation is used. The electricity mix comprises thermal (coal, natural gas and oil-fired), nuclear, wind and hydroelectric power plants, as well as bagasse-fired mills, which, besides exporting surplus electricity, also produce sugar and bioethanol. Oil and natural gas-derived fuels production and biodiesel fatty acid methyl-esters (FAME) derived from palm oil are also analyzed. It was found that in spite of the highest total unit exergy costs correspond to the production of biofuels and electricity, the ratio between the renewable to non-renewable invested exergy (cR/cNR) for those fuels is 2.69 for biodiesel, 4.39 for electricity, and 15.96 for ethanol, whereas for fossil fuels is almost negligible. Highlights: Total and non-renewable exergy costs of Brazilian transportation fuels are evaluated. Specific CO2 emissions in the production of Brazilian transportation fuels are determined. Representative production routes for fossil fuels, biofuels and electricity are reviewed. Exergoeconomy is used to distribute costs and emissions in multiproduct processes.